2014
DOI: 10.5339/gcsp.2014.19
|View full text |Cite
|
Sign up to set email alerts
|

Molecular candidates for cardiac stretch-activated ion channels

Abstract: The heart is a mechanically-active organ that dynamically senses its own mechanical environment. This environment is constantly changing, on a beat-by-beat basis, with additional modulation by respiratory activity and changes in posture or physical activity, and further overlaid with more slowly occurring physiological (e.g. pregnancy, endurance training) or pathological challenges (e.g. pressure or volume overload). Far from being a simple pump, the heart detects changes in mechanical demand and adjusts its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 159 publications
(180 reference statements)
0
55
1
Order By: Relevance
“…Mechanical stimulation activates a variety of ion channels in cardiac myocytes, including stretch-activated, nonselective cation channels and mechanosensitive potassium channels (2). The response of cells to mechanical deformation depends on the way the cells are being distorted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical stimulation activates a variety of ion channels in cardiac myocytes, including stretch-activated, nonselective cation channels and mechanosensitive potassium channels (2). The response of cells to mechanical deformation depends on the way the cells are being distorted.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, mechanical effects can modulate cardiac electrical activity in complex ways via mechanoelectric feedback (MEF) (2). It has been shown that a depolarizing stretch-activated current (I SAC ) through stretch-activated ion channels is evoked by the deformation of a cardiomyocyte (3,4), which affects its electrophysiological properties and excitation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include voltage-gated K + channels, inward rectifying K + channels, large-conductance Ca 2+ -activated K + channels, chloride channels (including cell-volume activated channels), voltage-gated proton channels, sodium-calcium exchangers, sodium-potassium ATPases, and stretch-activated channels [9092]. The latter include BK Ca , K ATP , and cation-nonselective stretch-activated channels, as well as the more recently described transient potential receptor family of ion channels such as TRPM7 [93], TRPV4 [93], and TRPC6 [94] (reviewed in detail elsewhere: [95, 96]).…”
Section: The Many Roles Of Scar Fibroblastsmentioning
confidence: 99%
“…29 Four years later, William Craelius and co-workers published the first MGC recordings from mammalian cardiomyocytes. 30 Since then, in addition to stretch-activated whole-cell currents, single-channel activity has been identified in a wide range of cardiac cells, 31 including atrial myocytes, 32 foetal 30 and (for potassium selective MGC at least) adult ventricular myocytes, 33 as well as cardiac non-myocytes. 27 …”
Section: Introduction To Cardiac Mechano-sensitivitymentioning
confidence: 99%